Whole Exome Sequencing in Females with Autism Implicates Novel and Candidate Genes - Butler, Merlin G. (Int J Mol Sci, 2015)
Classical autism or autistic disorder belongs to a group of genetically heterogeneous conditions known as Autism Spectrum Disorders (ASD). Heritability is estimated as high as 90% for ASD with a recently reported compilation of 629 clinically relevant candidate and known genes. We chose to undertake a descriptive next generation whole exome sequencing case study of 30 well-characterized Caucasian females with autism (average age, 7.7 ± 2.6 years; age range, 5 to 16 years) from multiplex families. Genomic DNA was used for whole exome sequencing via paired-end next generation sequencing approach and X chromosome inactivation status. The list of putative disease causing genes was developed from primary selection criteria using machine learning-derived classification score and other predictive parameters (GERP2, PolyPhen2, and SIFT). We narrowed the variant list to 10 to 20 genes and screened for biological significance including neural development, function and known neurological disorders. Seventy-eight genes identified met selection criteria ranging from 1 to 9 filtered variants per female. Five females presented with functional variants of X-linked genes (IL1RAPL1, PIR, GABRQ, GPRASP2, SYTL4) with cadherin, protocadherin and ankyrin repeat gene families most commonly altered (e.g., CDH6, FAT2, PCDH8, CTNNA3, ANKRD11). Other genes related to neurogenesis and neuronal migration (e.g., SEMA3F, MIDN), were also identified.